Flow Mahasiswa dalam Pembelajaran Daring Menggunakan Metode Belajar Group Investigation - Nugroho, Prasetyo Adi; Rosiana, Dewi; Hamdan, Stephani Raihana (Sukma: Jurnal Pendidikan, 2022)
Online learning during the Covid-19 pandemic is an alternative solution to keep the learning process running, including in universities. This study aims to find out what learning methods with group investigation (GI) methods are, which can improve the quality of the online learning experience and generate flow. This study uses a quantitative approach with an experimental design, namely between participant posttest only control group design. This study compares the effect of using two variants of the Group Investigation method on the flow experience felt by students when learning online. Participants in this study amounted to 27 people (96.3% women). The mean age of the participants was 21.4 years with a standard deviation of 1.12. The results showed that the use of two variants of the Group Investigation method gave the effect of flow with values that tended to be the same. The implication is that the two variants of the Group Investigation method can be used in online learning because they significantly produce student flow experiences in online learning.Pembelajaran daring selama Pandemi Covid-19 menjadi alternatif solusi yang dilakukan agar proses pembelajaran tetap berjalan, termasuk di perguruan tinggi. Penelitian ini bertujuan untuk mengetahui metode pembelajaran dengan metode group investigation (GI) seperti apa, yang dapat meningkatkan kualitas pengalaman belajar daring dan menghasilkan flow. Penelitian ini menggunakan pendekatan kuantitatif dengan desain eksperimental, yaitu between participant posttest only control group design. Penelitian ini membandingkan pengaruh penggunaan dua varian metode Group Investigation terhadap pengalaman flow yang dirasakan mahasiswa saat pembelajaran daring. Partisipan pada penelitian ini berjumlah 27 orang (96, 3 % perempuan). Rerata usia partisipan yaitu 21,4 tahun dengan standar deviasi sebesar 1,12. Hasil penelitian menunjukkan penggunaan dua varian metode Group Investigation memberikan pengaruh flow dengan nilai yang cenderung sama besarnya. Implikasinya, kedua varian metode Group Investigation dapat digunakan dalam pembelajaran daring karena secara signifikan menghasilkan pengalaman flow mahasiswa dalam pembelajaran daring.Â